Pengaruh Senam Kebugaran Jasmani Lansia (SKJ) terhadap Penurunan Tekanan Darah pada Pra Lansia Penderita Hipertensi - Tauriana , S.; Fauzi , Ahmad Kholid; Romadhon, Wimar Anugrah (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Hypertension if not treated immediately will cause complications of coronary heart disease, heart failure, damage to cerebral blood vessels, and kidney failure and even death. One of the causes of hypertension is lack of physical activity in pre-elderly. The purpose of this study was to determine the Effect of Elderly Physical Fitness Gymnastics (SKJ) on Reducing Blood Pressure in Pre-Elderly (49-59 Years) with Hypertension. Methods: The research design was a Quasi-experimental pre-post test with a pretest-posttest with control group design. A sample size of 25 pre-elderly intervention groups and 25 pre-elderly control groups were selected with inclusion and exclusion criteria. The independent variable is Physical Fitness Gymnastics and the dependent variable is Hypertension in pre-elderly. The instrument in this study was to measure blood pressure using a Sphygmomanometer and observation sheet. Statistical tests using Paired T-Test with a significance level of 0.0 Results: The results from the fourth week in the intervention group with a Paired T-test value of 0.001 or <0.050. Because the P value is smaller than the significance level (0.05) then (Ha) is accepted. So the conclusion is that there is an effect of Elderly Physical Fitness Gymnastics on Blood Pressure in Pre-Elderly (45-59 Years) with Hypertension. While the results of the Paired T-test in the control group were 0.574 or >0.050. Because the P value is greater than the significance level (0.05) then (Ha) is rejected. So the conclusion is that there is no effect of Blood Pressure in Pre-Elderly (45-59 Years) with Hypertension Conclusion: Physical Fitness Gymnastics needs to be carried out as a supporting therapy in treatment interventions to lower blood pressure in pre-hypertension elderly